A Revista do Ensino e a geografia escolar (1932 – 1942): inovações educacionais na Paraíba - Dias, Angélica Mara de Lima (2020)
The Revista do Ensino was an official organ of the educational press of the state of Paraíba that it published during the years 1932 to 1942, comprising a period marked by the educational renewal movement (inspired by the ideas of Escola Nova) and a nationalist policy undertaken by the government of Getúlio Vargas. In this sense, we believe that school geography was a fundamental discipline for the construction and consolidation of a modern, industrial and urban nation project. Given the context of national modernization in the 1930s, we understand that in Paraíba, the expansion of the ideals of Escola Nova and the Vargas government brought the dissemination of educational innovations aimed at teaching Geography and used the Revista do Ensino as a vehicle for disseminating such ideals in the State. Thus, in this research, we analyzed the role of Revista do Ensino (PB) in the dissemination of methodological innovations proposed for the teaching of Geography, in the period that it circulated; as well as the proposals of the Escola Nova for primary education in the state of Paraíba. When analyzing a local pedagogical Journal, we corroborate with André Chervel (1990) about the importance of research that values the study of school subjects and school culture. In addition to this author, others like Catani (1996); Albuquerque (2011) and Le Goff (2013) provided us with a theoretical basis on the subject addressed. As a methodological procedure, we focus on cataloging, analyzing, and systematizing the source information, that is, the copies of Revista do Ensino. The study of this form enabled us to understand the educational policy in Paraíba during the Vargas government, based on its methodological proposals, lessons and themes and the role of school geography in this process; as well as how the pedagogical forms are fertile for the understanding of the educational context in which they are inserted, constituting privileged sources for the understanding of school Geography.